Reliability of urinary dehydration markers in elite youth boxers - Zubac, D.; Cular, D.; Marusic, U. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the reliability and diagnostic accuracy of noninvasive urinary dehydration markers in field-based settings on a day-to-day basis in elite adolescent amateur boxers. Methods: Sixty-nine urine samples were collected daily from 23 athletes (17.3±1.9 y) during their weight-stable phase and analyzed by field and laboratory measures of hydration status. Urine osmolality (UOSM), urine specific gravity (USG), total protein content (TPC), and body-mass stability were evaluated to determine fluid balance and hydration status. Overall macronutrient and water intake were determined using dietary records. According to their anthropometric characteristics, athletes were assigned into 2 groups: lightweight (LWB) and heavyweight (HWB) boxers. Results: Data presented on UOSM demonstrated a uniform increment by 11.2%±12.8% (LWB) and 19.9%±22.7% (HWB) (P<.001) over the course of the study, even during the weight-stable phase (body mass, ICC=.99) and ad libitum fluid intake (42±4 mL/kgd). The intraclass correlation coefficients (ICCs) ranged from .52 to .55 for USG and .38 to .52 for UOSM, further indicating inconsistency of the urinary dehydration markers. Poor correlations were found between USG and TPC metabolites (r=.27, P=.211). Conclusions: Urinary dehydration markers (both USG and UOSM) exhibit high variability and seem to be unreliable diagnostic tools to track actual body-weight loss in real-life settings. The ad libitum fluid intake was apparently inadequate to match acute fluid loss during and after intense preparation. The applicability of a single-time-point hydration-status assessment concept may preclude accurate assessment of actual body-weight deficits in youth boxers.